2021
DOI: 10.3390/s21248496
|View full text |Cite
|
Sign up to set email alerts
|

Collision-Aware Routing Using Multi-Objective Seagull Optimization Algorithm for WSN-Based IoT

Abstract: In recent trends, wireless sensor networks (WSNs) have become popular because of their cost, simple structure, reliability, and developments in the communication field. The Internet of Things (IoT) refers to the interconnection of everyday objects and sharing of information through the Internet. Congestion in networks leads to transmission delays and packet loss and causes wastage of time and energy on recovery. The routing protocols are adaptive to the congestion status of the network, which can greatly impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(11 citation statements)
references
References 37 publications
(25 reference statements)
0
6
0
1
Order By: Relevance
“…(11) Collision-Aware Routing Using Multiobjective Seagull Optimization Algorithm for WSN-Based IoT [37]. Key points: this research proposed an optimization algorithm, namely multiobjective seagull optimization, for routing in a WSNenabled IoT environment.…”
Section: Deterministic Approachmentioning
confidence: 99%
“…(11) Collision-Aware Routing Using Multiobjective Seagull Optimization Algorithm for WSN-Based IoT [37]. Key points: this research proposed an optimization algorithm, namely multiobjective seagull optimization, for routing in a WSNenabled IoT environment.…”
Section: Deterministic Approachmentioning
confidence: 99%
“…The function is for accomplishing, suitable fitness by expressing the RE, network coverage, ND, and communication cost (CC). The parameters utilized from the clustering optimize are defined as follows [22]: The network coverage is determined as Eq. ( 11),…”
Section: Design Of Ysgf-c Techniquementioning
confidence: 99%
“…1 and Fig. 3 offer a comparative energy consumption (ECN) assessment of the IRSO-EAMHR model with recent models such as fully distributed energy aware multi-level clustering and routing (FDE), Energy-Efficient Optimal Multi-path Routing Protocol (EEOMPRP), Wolf optimization for multi-path routing protocol (WOMPR), CoAP congestion control for the internet of things (CoAP-IOT), and Collision-Aware Routing Using Multi-Objective Seagull Optimization Algorithm (CAR-MOSOA)under distinct nodes [18][19][20][21][22]. The results indicated that the IRSO-EAMHR model has resulted in effectual outcome with lower ECN over the other algorithms under distinct count of nodes.…”
Section: Experimental Analysismentioning
confidence: 99%